Possible inhibitory effects of terbinafine on aripiprazole metabolism: Two case reports - Ian R. McGrane, PharmD; Tori J. Lindbloom, PharmD candidate; Robert C. Munjal, MD (American Association of Psychiatric Pharmacists, 2021)
Aripiprazole, an atypical antipsychotic, is a metabolic substrate for cytochrome P450 (CYP)3A4 and 2D6. Terbinafine, an antifungal agent used for onychomycosis, is a CYP2D6 inhibitor and could theoretically reduce the metabolism of aripiprazole. However, there are no published reports describing this interaction. We present 2 female patients hospitalized in a psychiatric unit who were both taking aripiprazole 15 mg daily and terbinafine 250 mg daily prior to admission. The first patient was a 58-year-old female who was prescribed aripiprazole and terbinafine concomitantly for approximately 5 months prior to admission. A commercial pharmacogenetic testing platform classified this patient as a normal metabolizer for CYP3A4 and 2D6. The first patient's serum trough aripiprazole concentration at steady-state concentration (Css) was 207.5 ng/mL. The second patient was a 43-year-old female who was taking aripiprazole and terbinafine concomitantly for approximately 2 weeks prior to admission who had a Css aripiprazole concentration of 278.9 ng/mL. Aripiprazole has a wide therapeutic range (100 to 350 ng/mL) and a reference dose-related drug concentration of 11.7 (mean)±5.6 (SD) ng/mL/mg/d. Our patients had Css aripiprazole concentrations 18% and 59% higher than guideline-supported dose-related drug concentrations. Through the use of therapeutic drug monitoring, pharmacogenetic data, electronic pharmaceutical claims data, and the Drug Interaction Probability Scale, we suggest terbinafine possibly increases aripiprazole concentrations 18% to 59%. Further reports are needed to confirm these findings prior to using this information in clinical practice.